Dental Pulp Stem Cell Polarization: Effects of Biophysical Factors. (September 2021) - Chang, B.; Ma, C.; Feng, J.; Svoboda, K.K.H.; Liu, X.
Dental pulp stem cells (DPSCs) have the potential to polarize, differentiate, and form tubular dentin under certain conditions. However, the factors that initiate and regulate DPSC polarization and its underlying mechanism remain unclear. Identification of the factors that control DPSC polarization is a prerequisite for tubular dentin regeneration. We recently developed a unique bioinspired 3-dimensional platform that is capable of deciphering the factors that initiate and modulate cell polarization. The bioinspired platform has a simple background and confines a single cell on each microisland of the platform; therefore, it is an effective tool to study DPSC polarization at the single-cell level. In this work, we explored the effects of biophysical factors (surface topography, microisland area, geometry, tubular size, and gravity) on single DPSC polarization. Our results demonstrated that nanofibrous architecture, microisland area, tubular size, and gravity participated in regulating DPSC polarization by influencing the formation of the DPSC process and relocation of the Golgi apparatus. Among these factors, nanofibrous architecture, tubular size, and appropriate microisland area were indispensable for initiating DPSC polarization, whereas gravity served as an auxiliary factor to the process of DPSC polarization. Meanwhile, microisland geometry had a limited effect on DPSC polarization. Collectively, this work provides information on DPSC polarization and paves the way for the development of new biomaterials for tubular dentin regeneration.